Correlation of clinical data and the Alvarado's Score as predictors of acute appendicitis - Cunha,Carlos Magno Queiroz da (2018)
ABSTRACT Objective: To correlate the patient's clinical data and the Alvarado's Score as predictors of acute appendicitis. Methods: This is an observational, descriptive and prospective study performed at a public urgency and emergency hospital in the city of Fortaleza, Ceará, between July and December 2016, with 34 patients undergoing open appendectomy with ages between 18 and 70 years. Statistical analysis was performed using the SPSS program. Results: The following statistical correlations were performed: number of days with abdominal pain until the operative event and degree of inflammation according to a macroscopic analysis of the appendix, Alvarado's Score and number of days with abdominal pain until the operative event, Alvarado's Score and degree of inflammation according to a macroscopic analysis of the appendix, number of days with abdominal pain until the operative event, and number of days of hospitalization in the postoperative period, degree of inflammation according to amacroscopic analysis of the appendix, number of days of hospitalization in the postoperative period and Alvarado's Score, and number of days of hospitalization in the postoperative period; the first five correlations were statistically significant (p < 0.05). Conclusion: The use of this Alvarado's Score in health services emerges as a tool for the diagnosis of acute appendicitis.